A rice R2R3‐MYB (OsC1) transcriptional regulator improves oxidative stress tolerance by modulating anthocyanin biosynthesis. Issue 4 (17th October 2021) - Upadhyaya, Gouranga; Das, Arup; Ray, Sudipta
Abstract: The R2R3 type MYB transcription factors participate in controlling flavonoid production in plants, including anthocyanin and proanthocyanin. Black rice with high anthocyanin content is an important candidate for understanding R2R3‐MYB‐based regulation of the anthocyanin biosynthesis pathway (ABP). This study was undertaken to draw the functional relationship of an R2R3‐MYB protein with anthocyanin biosynthesis and oxidative stress tolerance in plants. The expression levels of the late ABP genes in the panicle stage of black rice were in good agreement with the accumulation of anthocyanin, especially cyanidin 3‐glucoside. Among all MYB genes present in rice, an R2R3 type ( C1 ) regulates anthocyanin biosynthesis and was studied further. The positive correlation between the expression of ABP genes and OsC1 along with the nuclear localization of OsC1 are in line with its possible involvement as a transcriptional regulator of ABP genes. Interestingly, OsC1 overexpressed in white rice plants triggered anthocyanin production through augmentation of the transcript level of late ABP genes. Moreover, OsC1 ‐transformed plants exhibited a lower amount of reactive oxygen species upon exposure to oxidative stress. The increased anthocyanin content in white rice seedlings resulted in higher photosynthetic efficiency, less membrane damage and consequently lower oxidative stress. The OsC1 transcriptional regulator helps to ameliorate oxidative stresses in plants owing to its anthocyanin modulating ability.